Hospital classes in the Northeast Region of Brazil: a constitutional right - Renata Souza de Lima; Edna Cristina do Prado (Universidade Estadual de Alagoas, 2021)
This study presents a bibliographic review and a documental research about the pedagogical care in hospital environment as a constitutional right, seeking to inventory the legislation of the Northeast Region of Brazil about the hospital teaching work, as well as to perform an analysis of the current context of this type of care in Alagoas. For this purpose, a consultation was made to the websites of the official agencies of states and municipalities of that region, with the objective of understanding how the right to this type of educational assistance by the public power is realized -or not. The results allow us to state that the Northeast region has not yet been able to guarantee the effectiveness of the constitutional right to education, whether due to the absence of legal provisions or public policies aimed at children and young people in detention contexts.